Effect of Stemona curtisii root extract on P-glycoprotein and MRP-1 function in multidrug-resistant cancer cells - Limtrakul P. (2014)
Multidrug resistance (MDR) is the result of overexpression of membrane bound proteins that efflux chemotherapeutic drugs from the cells. Two proteins, P-glycoprotein (P-gp) and multidrug-resistance associated protein-1 (MRP-1) efflux chemotherapeutic agents out of the cancer cell that decrease intracellular drug accumulation, thereby decreasing the effectiveness of many chemotherapeutic agents. In the present study, the ethanolic extract of the roots of Stemona curtisii Hook. was tested for the potential ability to modulate the MDR phenotype and function of P-gp and MRP-1. The S. curtisii extract reversed the resistance to putative chemotherapeutic agents, including vinblastine, paclitaxel and colchicine of KB-V1 cells (MDR human cervical carcinoma with high P-gp expression) in a dose-dependent manner, but not in KB-3-1 cells (drug sensitive human cervical carcinoma, which lack P-gp expression). The root extract also increased the intracellular uptake and retention of 3[H]-vinblastine in KB-V1 cells dose dependently. The extract did not influence MDR phenotype-mediated MRP-1 in MRP1-HEK293 (human embryonic kidney cells stably transfected with pcDNA3.1-MRP1-H10 which show high MRP-1 expression) and pcDNA3.1-HEK293 (wild type). In summary, the S. curtisii root extract modulated P-gp activity but not MRP-1 activity. The result obtained from this study strongly indicated that S. curtisii extract may play an important role as a P-gp modulator as used in vitro and may be effective in the treatment of multidrug-resistant cancers. The purified form of the active components of S. curtisii extract should be investigated in more details in order to explain the molecular mechanisms involved in P-gp modulation. This is the first report of new biological activity in this plant, which could be a potential source of a new chemosensitizer. © 2007 Elsevier GmbH. All rights reserved.